Honduras : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2006)
Honduras's First Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria are discussed. The authorities are taking measures to contain inflation. The inflation target has been raised to accommodate the first-round impact of the oil price increase, and measures to limit foreign borrowing and credit growth are being taken to restrain domestic liquidity in the face of high foreign exchange inflows. A cautious monetary policy is particularly important given the role of expected inflation in wage settlements.